GOAL-ORIENTATION CULTURE AND JOB COMMITMENT AMONG LECTURERS IN PUBLIC UNIVERSITIES IN KENYA - Mutiso Pauline Mwikali*, Jeremiah M. Kalai, Ursula Okoth, Per-Olof Hansson (International Journal of Research Science and Management, 2023)
Goal orientation helps people and organizations to focus their efforts towards achievement of individual and organizational objectives and goals. Whereas previous scholars have documented that learning goal orientation and performance goal orientation are significant in influencing employee behaviour, how these orientations influence job commitment among university lecturers is still a matter of conjecture. This knowledge would be significant especially in the context of public universities in Kenya where missing lecture sessions are rampant on one hand, while more employers prefer graduates from Technical, Industrial and Vocational Enterprise Training (TIVET) institutions than university graduates, on the other hand. This study explored the influence of goal orientation culture on job commitment among lecturers at the University of Nairobi and South Eastern University. The hypothesis that: There is no significant relationship between goal orientation culture and job commitment among lecturers was tested. Self-determination theory (SDT) of motivation originated by Ryan and Deci was used to guide the study. Descriptive survey design was used on a target population of 56191 lecturers, Deans and students from which 377 was derived as a sample size via Krejcie and Morgan’s (1970) Table. Closed and open-ended questionnaire was used for data collection, and regressions (at 0.05 level of significance) as well as thematic analyses used respectively to analyse quantitative and qualitative data. Findings revealed that 86.1% of changes in job commitment among the lecturers is attributed to goal-oriented culture (R2 =0.861), with goals related to timelines for examination result submission and number of units taught strictly adhered to. It is concluded that matching of the university and lecturers’ goals related to teaching timelines among others significantly enhance lecturers’ job commitment. Professional development opportunities for lecturers should be enhanced to improve their capacities, while challenges facing lecturers in enhancing their job commitment need further exploration.